Experimental Study on impact of longitudinal reinforcement ratio on deformation capacity of self-compacting high strength concrete beam - Lee, Yuan Jake (Universiti Teknologi PETRONAS, 2018)
Ordinary reinforced concrete is brittle and low strength. To achieve high strength properties, low water cement ratio is required which affects the strain of concrete. Therefore, high strength self-compacting concrete (HSSCC) is developed as it exhibit good strength and strain performance. However, there are lack of studies of the relationship between HSSCC and longitudinal ratio. More investigation is required. Hence, this research focuses on experimentally evaluate the deformation capacity of different longitudinal reinforcement ratio for HSSCC beam with high compressive strength and compare the deformation capacity of HSSCC with and without steel fiber. To achieve the objective, mechanical properties of concrete- compressive strength, split cylinder test, dog bone tensile test and flexure test were tested after 7 days and 28 days of curing. Furthermore, flexure failure mode of three beam were tested. The compressive strength of mixture design A (mix design without steel fiber) and mixture design B (mix design with steel fiber) is 91.42 KN and 97.65 KN. The average tensile test of mixture A and B is 5KN and 8.78KN. The failure mode of beam A01S (mix design A with single reinforcement) is diagonal tension failure; beam B01S and B01D (mix design B with single and double reinforcement) suffer reinforcement fracture. The maximum load capacity of beam increased approximately 25KN after added 3% of steel fiber into mixture design. However, strain performance of steel fiber is lower as the longitudinal reinforcement ratio of beam increase. More studies required to investigate the relationship of steel fiber and different longitudinal reinforcement ratio.